2015
DOI: 10.1007/s11357-015-9758-0
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and leukocyte telomere length in a multi-ethnic elderly population

Abstract: Leukocyte telomere length (LTL) is considered as the marker of biological aging and may be related to environmental factors. The current study aimed to examine the relation between Mediterranean-type diet and LTL. We used a cross-sectional study of 1743 multi-ethnic community residents of New York aged 65 years or older. Mediterranean-type diet (MeDi) was calculated from dietary information collected using a food frequency questionnaire. LTL was measured from leukocyte DNA using a real-time PCR method to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
1
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 64 publications
(50 reference statements)
1
78
1
6
Order By: Relevance
“…La adhesión a patrones dietéticos que incluyen un consumo elevado de una amplia variedad de alimentos vegetales y bajo consumo de alimentos altamente procesados, como la dieta mediterránea, parece ser la forma más evidente de prevenir el desgaste de los telómeros (42,46,152,167). Cabe señalar que solo tres de los estudios con resultados significativos en relación con la asociación entre los patrones dietéticos y TL evaluaron la calidad de la dieta (147,156,164).…”
Section: Resultados Y Discusiónunclassified
See 3 more Smart Citations
“…La adhesión a patrones dietéticos que incluyen un consumo elevado de una amplia variedad de alimentos vegetales y bajo consumo de alimentos altamente procesados, como la dieta mediterránea, parece ser la forma más evidente de prevenir el desgaste de los telómeros (42,46,152,167). Cabe señalar que solo tres de los estudios con resultados significativos en relación con la asociación entre los patrones dietéticos y TL evaluaron la calidad de la dieta (147,156,164).…”
Section: Resultados Y Discusiónunclassified
“…Puede ser que exista un mayor efecto del envejecimiento en ciertas etnias que deje "menos espacio" al estilo de vida y a otros factores ambientales para modular la LTL. Además, se ha demostrado que la inflamación subyacente o el estado oxidativo pueden diferir entre diferentes grupos étnicos (152). Por lo tanto, estos factores pueden haber contribuido a la variación de los resultados entre los estudios mencionados.…”
Section: Resultados Y Discusiónunclassified
See 2 more Smart Citations
“…In line with the evidence on diet and inflammation, several studies have observed longer blood TL among individuals with higher Alternative Healthy Eating Index scores or higher Mediterranean diet scores [3538]. Further studies have reported associations between blood TL and specific foods or nutrients.…”
Section: Introductionmentioning
confidence: 70%